Why we should be more careful using hydroxychloroquine in influenza season during COVID-19 pandemic?. (January 2021) - Çelik, Hülya Gamze; Keske, Şiran; Şener, Ülker; Tekbaş, Müge; Kapmaz, Mahir; Şahin, Şükrü Taylan; Özyıldırım, Aslı; Aytekin, Saide; Aytekin, Vedat; Ergönül, Önder
Highlights: Hydroxychloroquine use increases the risk of QT prolongation among patients with coronavirus disease 2019 (COVID-19). Using concomitant oseltamivir and hydroxychloroquine increased the risk of QT prolongation. Having diabetes mellitus increased the risk of QT prolongation. Patients receiving hydroxychloroquine should be monitored closely. Abstract: The aim of this study was to describe the QTc prolongation and related adverse cardiac events during the administration of hydroxychloroquine (HCQ) and its combinations for the treatment of coronavirus disease 2019 (COVID-19). Hospitalized patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) who received HCQ and had initial and follow-up electrocardiograms performed between March 10 and May 30, 2020 were included. Critical QTc prolongation was detected in 12% of the patients. On multivariate analysis, diabetes mellitus (odds ratio 5.8, 95% confidence interval 1.11–30.32, p = 0.037) and the use of oseltamivir (odds ratio 5.3, 95% confidence interval 1.02–28, p = 0.047) were found to be associated with critical QTc prolongation.